Previous account on the order Scorpaeniformes (Actinopterygii: Teleostei) in the collection of the Laboratory of Ichthyology (Department of Biological Sciences) of the State University of Feira de Santana (Bahia) - Lopes, Paulo R. D.; Silva, Gilvanete R. da (SITIENTIBUS série Ciências Biológicas, 2002)
The Scorpaeniformes collection deposited in the Laboratory of Ichthyology (Department of Biological Sciences) of the State University of Feira de Santana is presented. It was analised a total of 85 lots and 182 specimens from the region between the states of Pernambuco and Rio Grande do Sul, Brazil. Three families and nine species were identified: Dactylopteridae: Dactylopterus volitans; Scorpaenidae: Scorpaena brasiliensis, S. isthmensis and S. plumieri; Triglidae: Bellator brachychir, Peristedion altipinne, Peristedion sp., Prionotus nudigula and P. punctatus.